The truth about leadership : the no-fads, heart-of-the-matter facts you need to know - Kouzes, James M., 1945-; Posner, Barry Z. (San Francisco, CA : Jossey-Bass, 2010)
"A fresh look at what it means to lead from two of the biggest names in leadership In these turbulent times, when the very foundations of organizations and societies are shaken, leaders need to move beyond pessimistic predictions, trendy fads, and simplistic solutions. They need to turn to what's real and what's proven. In their engaging, personal, and bold new book, Kouzes and Posner reveal ten time-tested truths that show what every leader must know, the questions they must be prepared to answer, and the real-world issues they will likely face. Based on thirty years of research, more than one million responses to Kouzes and Posner's leadership assessment, and the questions people most want leaders to answer. Explores the fundamental, enduring truths of leadership that hold constant regardless of context or circumstance-leaders make a difference, credibility, values, trust, leading by example, heart, and more. Shows emerging leaders what they need to know to be effective; fans of The Leadership Challenge will find a dynamic new look at the real challenges leaders face today. Drawing from cases spanning three generations of leaders from around the world, this is a book leaders can use to do their real and necessary work-bringing about the essential changes that will renew organizations and communities."--
Introduction: What Everyone Wants to Know About Leadership -- Truth 1: You Make a Difference -- Truth 2: Credibility Is the Foundation of Leadership -- Truth 3: Values Drive Commitment -- Truth 4: Focusing on the Future Sets Leaders Apart -- Truth 5: You Can't Do It Alone -- Truth 6: Trust Rules -- Truth 7: Challenge Is the Crucible of Greatness -- Truth 8: You Either Lead by Example or You Don't Lead at All -- Truth 9: The Best Leaders Are the Best Learners -- Truth 10: Leadership Is an Affair of the Heart.
Includes bibliographical references and index.
Keywords: Leadership; Executive ability